Is color a matter of concern during microplastic exposure to Scenedesmus obliquus and Daphnia magna? - Chen, Qiqing; Li, Yue; Li, Bowen (Journal of hazardous materials, 2020)
[Display omitted] •Algal growth increased first and then decreased with increasing MP concentrations.•Green MPs did not affect algal cell locomotion due to particle resemblance.•White MPs may inhibit the algal growth due to ethanol residue presence.•Daphnia cannot distinguish similar sized algae and MPs.•Algae will aggregate with MPs and did not affect Daphnia ingestion in long run. Toxicities of microplastics (MPs) on aquatic organisms have been widely investigated often by using white or transparent MPs. However, various colored MPs scatter in the real aquatic environment. Here we investigated four colored MPs’ effects on Scenedesmus obliquus algal growth first. Under the light condition, algal growth increased initially due to hormesis stimulation and then decreased gradually at higher MP concentrations. Green colored MPs exhibited the lowest inhibition effect, probably due to their resemblance to algae; white MPs inhibited the algal growth significantly, which was attributed to the presence of ethanol. Turbulence condition seemed to diminish algal growth differences among groups, but it led to slight oxidative stress. Furthermore, we also tested MP effects on Daphnia magna feeding ability. Results indicated that daphnids were probably not able to distinguish colored MPs from algae. But their algae ingestion amounts increased when MPs reached to 40% of algal cells, probably because daphnids could widen their filtering gapes when food quality decreases. However, this phenomenon did not last until the 3rd day, as the agglomeration of MPs and algae made them settle down. Overall, our results highlighted the color may alter some MP effects and is necessary to be considered in (eco)toxicological studies.